Experiences of Undergraduate Nursing Students Learning Psychomotor Skills During the Covid-19 Pandemic: A Qualitative Study - Çiftçi, Bahar; Yıldız, Güzel Nur; Uzan, Muruvvet Demiral (My University, 2024)
Objective: This study aimed to examine the experiences of nursing students learning psychomotor skills during the COVID-19 pandemic, the problems they experienced in this process, and their feelings and needs. Methods: This was a qualitative phenomenological study. The research was analyzed descriptively and thematically. The research was conducted in Erzurum in January 2022. The population of the study consisted of 2nd-year students studying at the Atatürk University Faculty of Nursing in the fall semester of the 2021–2022 academic year. The sample consisted of four second-year undergraduate nursing students selected by the criterion sampling method. The research data were collected with an ‘Introductory Information Form’ and a ‘Semistructured Questionnaire’. The content analysis method was used to evaluate the qualitative data. Results: Four themes and three subthemes were identified as a result of the analysis of the data obtained from the interviews with the students. The main themes are inefficiency, expectations from the instructor, emotions, and active learning. It was determined that inefficiency was categorized under the subthemes of “Problems experienced in online education and the limitation of online education in terms of learning psychomotor skills” and “Reasons for inefficiency”. It was determined that there were no subthemes in the themes of expectations from the instructor and emotions. Active learning was found to be under the subtheme of “Getting more efficiency from homework rather than what the instructors teach”. Conclusions: The online education process was inadequate for learning the psychomotor skills of nursing students.
Keywords: Sağlık Bilimleri ve Hizmetleri; Hemşirelik